Pemahaman Fiqh Dan Praktik Qunut Subuh Pada Masyarakat Awam Di Tengah Keberagaman Mazhab - Sri Ajizah Idhayani; Feriska Amalia Putri; Zuan Faza Sulistya; Viki Karimatul Adlimah; Siyono (Yayasan Nanggroe Aceh Mulia, 2026)
This study examines the understanding of fiqh and the practice of the Subuh qunut among lay Muslims in Indonesia amid diverse Islamic legal schools. Using library research and a philosophical approach, this paper analyzes classical and contemporary literature to explore how fiqh literacy, social environments, and religious authorities shape public perceptions and practices. The findings show that most lay Muslims perform the Subuh qunut based on local traditions and the authority of religious leaders rather than direct engagement with textual evidences. Variations in qunut practice are strongly influenced by exposure to different mazhab teachings, digital religious content, and socio-religious backgrounds. The differences among the four major Sunni schools Syafi‘i, Hanafi, Maliki, and Hanbali—also contribute to diverse ritual expressions in Indonesian communities. Despite these variations, all mazhab agree that the presence or absence of the Subuh qunut does not affect the validity of the prayer. The study concludes that enhancing fiqh literacy and promoting religious moderation are essential to prevent minor ritual differences from causing social tension. Strengthening tolerance and cross-mazhab understanding can help maintain harmony in Indonesia’s plural Muslim society.